Early time‐restricted eating compared with daily caloric restriction: A randomized trial in adults with obesity. Issue 5 (26th April 2022) - Thomas, Elizabeth A.; Zaman, Adnin; Sloggett, Kelsey J.; Steinke, Sheila; Grau, Laura; Catenacci, Victoria A.; Cornier, Marc‐Andre; Rynders, Corey A.
Abstract: Objective: This trial aimed to evaluate the acceptability and efficacy of early time‐restricted eating plus daily caloric restriction (E‐TRE+DCR) compared with DCR alone within a behavioral weight‐loss intervention. Methods: Participants ( n = 81, 69 women, mean [SD] age: 38.0 [7.8] years, BMI: 34.1 [5.7] kg/m 2 ) were randomized to E‐TRE (10‐hour eating window starting within 3 hours of waking) plus DCR or DCR alone ( 35% DCR) for 39 weeks. The primary outcome was body weight (measured with digital scale) at week 12. Secondary outcomes measured at week 12 included hemoglobin A1c, lipids, energy intake (photographic food records), physical activity (accelerometry), dietary adherence (questionnaires), and body composition (dual‐energy x‐ray absorptiometry). Weight and body composition were also assessed at week 39. Results: Mean [SD] weight loss was not different between groups at week 12 (E‐TRE+DCR: −6.2 [4.1] kg vs. DCR: −5.1 [3.2] kg) or at week 39 (E‐TRE: −4.9 [5.3] kg vs. DCR: −4.3 [5.3] kg). There were no between‐group differences in changes in body composition, dietary adherence, energy intake, physical activity, hemoglobin A1c, or lipids at week 12. Conclusions: E‐TRE+DCR was found to be an acceptable dietary strategy, resulting in similar levels of adherence and weight loss compared with DCR alone.